THE EXPERIENCE OF THE NEW NURSE EDUCATOR: THE FIRST YEAR OF TRANSITION: A REVIEW OF THE LITERATURE - Phillips, Claudia (Acta Scientiae et Intellectus, 2024)
The transition from the role of nurse clinician to nurse educator has been said to be a difficult journey. A review of the literature was undertaken to investigate the causes that create such a difficult transition. The following question guided the literature review as well as the discussion of such: What is the experience of the new nurse educator during the first year of transition? And what are the recommendations, if any, to assist those taking on this transition? As the literature was reviewed common themes began to emerge such as old vs. new role, interpersonal struggles, lack of preparation and guidance, politics and social aspects. These are reviewed in detail in the following discussion. Recommendations for practice to ease the transition also began to emerge and the literature was reviewed. It became apparent that an equal partnership between schools of nursing and new nurse educators was crucial to making transitions as smooth as possible as well as successful. These are also detailed in the following discussion.